Task Performance Modulates Functional Connectivity Involving the Dorsolateral Prefrontal Cortex in Patients with Schizophrenia - Wu, Shihao; Wang, Huiling; Chen, Cheng; Zou, Jilin; Huang, Huan; Li, Peifu; Zhao, Yilin; Xu, Qizhong; Zhang, Liang; Wang, Hesheng; Pandit, Sanjib; Dahal, Subodh; et al. (Frontiers in Psychology, 2017)
Past researches have suggested that in regard to working memory-induced dorsolateral prefrontal cortex (DLPFC) activation and connectivity differences between patients with schizophrenia and healthy controls have not reached a consistent result. The functional integration perspective further suggests that working memory performance also modulates group differences in functional interactions of the DLPFC between patients and controls. To explore this possibility, forty-five healthy controls and forty-five patients with schizophrenia were recruited to perform a 2-back task during functional magnetic resonance imaging (fMRI). Each group was further divided into two subgroups based on task performance in order to examine the modulatory effect of performance on functional interactions of the DLPFC, as measured via psychophysiological interaction (PPI) analyses. We observed that, in patients with schizophrenia who exhibited impaired working memory capacity and decreased brain activation/deactivation, functional interactions between the right/left DLPFC and angular cortex were decreased relative to those of healthy controls. More importantly, we observed an interaction effect of working memory performance and diagnosis on functional connectivity between the right/left DLPFC seed region and posterior regions such as the angular cortex, fusiform gyrus, and middle occipital gyrus. This interaction effect was mainly driven by the negative correlation between functional connectivity and performance in healthy controls but by the positive correlation in patients with schizophrenia. These results demonstrate the differential effects of inter-individual differences in working memory performance on the functional interaction between the DLPFC and posterior regions in patients with schizophrenia compared to healthy controls, which may shed new light on the neural basis of working memory. Keywords: Schizophrenia, N-back, fMRI, Psychophysiological Interaction (PPI), Dorsolateral Prefrontal Cortex (DLPFC), Fusiform Gyrus, Inferior Parietal Lobule (IPL)